Female Entrepreneurship as Subject of Research - Gomes, Almiralva Ferraz; Santana, Weslei Gusmão Piau; Araújo, Uajará Pessoa; Martins, Caroline Miriã Fontes (Review of Business Management, 2014)
This paper’s main goal is to study the literature produced about “female entrepreneurship”, so as to scrutinize and deepen scientific reasoning referring to women entrepreneurs whilst investigating the degree of theoretical consolidation this field of knowledge has achieved. To this end, and from a critical perspective, we assessed research published in Brazilian and international journals from 1970 on, so as to offer a systematic review of the object in focus. Despite the contributions given by previous research – which does, after all, provide us with relevant information and data concerning women entrepreneurs –, most of it merely describes small segments of the female entrepreneur population, and does not advance in applying or developing theories. Moreover, in most cases, research was quantitative and empirical and attempted to draw a “profile” of women entrepreneurs. Few studies specifically carried out a theoretical analysis on the topic “gender”. Apparently, the main concern of many of these studies was to focus on the sexual structure of organizations and on its impact upon business activities. Thus, it seems appropriate to use new points-of-view to study the “female entrepreneurship” phenomenon – or, at least, to establish new ideas for investigation.